Human Liver Stem Cell-Derived Extracellular Vesicles Target Hepatic Stellate Cells and Attenuate Their Pro-fibrotic Phenotype - Giulia Chiabotto; Giulia Chiabotto; Elena Ceccotti; Elena Ceccotti; Marta Tapparo; Marta Tapparo; Giovanni Camussi; Giovanni Camussi; Stefania Bruno; Stefania Bruno (Frontiers in Cell and Developmental Biology, 2021)
Liver fibrosis occurs in response to chronic liver injury and is characterized by an excessive deposition of extracellular matrix. Activated hepatic stellate cells are primarily responsible for this process. A possible strategy to counteract the development of hepatic fibrosis could be the reversion of the activated phenotype of hepatic stellate cells. Extracellular vesicles (EVs) are nanosized membrane vesicles involved in intercellular communication. Our previous studies have demonstrated that EVs derived from human liver stem cells (HLSCs), a multipotent population of adult stem cells of the liver with mesenchymal-like phenotype, exert in vivo anti-fibrotic activity in the liver. However, the mechanism of action of these EVs remains to be determined. We set up an in vitro model of hepatic fibrosis using a human hepatic stellate cell line (LX-2) activated by transforming growth factor-beta 1 (TGF-β1). Then, we investigated the effect of EVs obtained from HLSCs and from human bone marrow-derived mesenchymal stromal cells (MSCs) on activated LX-2. The incubation of activated LX-2 with HLSC-EVs reduced the expression level of alpha-smooth muscle actin (α-SMA). Conversely, MSC-derived EVs induced an increase in the expression of pro-fibrotic markers in activated LX-2. The analysis of the RNA cargo of HLSC-EVs revealed the presence of several miRNAs involved in the regulation of fibrosis and inflammation. Predictive target analysis indicated that several microRNAs (miRNAs) contained into HLSC-EVs could possibly target pro-fibrotic transcripts. In particular, we demonstrated that HLSC-EVs shuttled miR-146a-5p and that treatment with HLSC-EVs increased miR-146a-5p expression in LX-2. In conclusion, this study demonstrates that HLSC-EVs can attenuate the activated phenotype of hepatic stellate cells and that their biological effect may be mediated by the delivery of anti-fibrotic miRNAs, such as miR-146a-5p.